Perspectives on Individual Animal Identification from Biology and Computer Vision. (29th May 2021) - Vidal, Maxime; Wolf, Nathan; Rosenberg, Beth; Harris, Bradley P; Mathis, Alexander
Synopsis: Identifying individual animals is crucial for many biological investigations. In response to some of the limitations of current identification methods, new automated computer vision approaches have emerged with strong performance. Here, we review current advances of computer vision identification techniques to provide both computer scientists and biologists with an overview of the available tools and discuss their applications. We conclude by offering recommendations for starting an animal identification project, illustrate current limitations, and propose how they might be addressed in the future.